Interactions Between Environment and Genetic Diversity in Perennial Grass Phenology: A Review of Processes at Plant Scale and Modeling - Rouet, Simon; Barillot, Romain; Leclercq, Denis; Bernicot, Marie-Hélène; Combes, Didier; Escobar-Gutiérrez, Abraham; Durand, Jean-Louis (Frontiers in Plant Science, 2021)
In perennial grasses, the reproductive development consists of major phenological stages which highly determine the seasonal variations of grassland biomass production in terms of quantity and quality. The reproductive development is regulated by climatic conditions through complex interactions subjected to high genetic diversity. Understanding these interactions and their subsequent consequences on plant development and growth is essential to optimize grassland management and identify the potential consequences of climate change. Here, we review the main stages of reproductive development, from floral induction to heading, i.e. spike emergence, considering the effect of the environmental conditions and the genetic diversity observed in perennial grasses. We first describe the determinants and consequences of reproductive development at the individual tiller scale before examining the interactions between plant tillers and their consequences on grassland perenniality. Then, we review the available grassland models through their ability to account for the complexity of reproductive development and genetic × environmental interactions. This review shows that : 1) The reproductive development of perennial grasses is characterized by a large intraspecific diversity which has the same order of magnitude than the diversity observed between species or environmental conditions. 2) The reproductive development is determined by complex interactions between the processes of floral induction and morphogenesis of the tiller. 3) The perenniality of a plant is dependent on the reproductive behavior of each single tiller. 4) Published models only partly explain the complex interactions between morphogenesis and climate on reproductive development. 5) Introducing more explicitly the underlying processes involved in reproductive development in models would improve our ability to anticipate grasslands behavior in future growth conditions.